Empowering Resilience Among Female Breadwinners in South West, Nigeria - Motolani, Williams Taiwo; O, Ayodele Kolawole; A, Aderanti Ruth; Olugbenga, Ajayi (Journal of Posthumanism, 2026)
The clamour for gender equality in many societies in Africa is ongoing. This task may seem herculean but it is achievable with constant enlightenment of both males and females alike. The indigenous woman is compelled to obey their husbands since the indigenous society is largely patriarchal. Thus, exposing them to persistent and uncontrolled violation of their rights, privileges and freedom. The significant role of the woman in the economic development of a Nation cannot be overemphasized. Unfortunately, women over time have been limited in their roles but rather confined to the traditional gender roles which prevent expression. This paper discusses the indigenous women as breadwinners vis-a-vis their roles and responsibilities in the family. It also sheds light on how the empowerment of resilience in women can be prioritised. Education, regular training and provision of resources by the Government and Non- Governmental bodies have been suggested as potent ways at empowering resilience in the indigenous women.